2020
DOI: 10.1098/rsta.2019.0491
|View full text |Cite
|
Sign up to set email alerts
|

Underway velocity measurements in the Alderney Race: towards a three-dimensional representation of tidal motions

Abstract: The Alderney Race, located northwest of the Cotentin Peninsula (France), is a site with high tidal-stream energy potential. Circulation through the Alderney Race is complex, with current speed exceeding 3 m s −1 at neap tide. Towed acoustic Doppler current profiler (ADCP) measurements and static point velocity measurements were performed in July 2018 focusing on assessment of circulation and vertical structure of tidal currents. Transect surveys revealed peculiar features of local dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…This may be related to either the limitations in turbulence modelling referred to above or an underestimation of the bathymetric step effect in the modelled flow. In this same region, Sentchev et al [7] found strong gradients on measured current velocity profiles, which shifted from highly sheared over the 30 m plateau located in the centre of our domain to nearly homogeneous at the point where the radar measured a sudden change in the sign of vorticity.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This may be related to either the limitations in turbulence modelling referred to above or an underestimation of the bathymetric step effect in the modelled flow. In this same region, Sentchev et al [7] found strong gradients on measured current velocity profiles, which shifted from highly sheared over the 30 m plateau located in the centre of our domain to nearly homogeneous at the point where the radar measured a sudden change in the sign of vorticity.…”
Section: Discussionsupporting
confidence: 60%
“…They suggested that the turbulence measured during the ebb tide had been generated upstream, and advected southward by the tidal current to their measurement site. In their work, Sentchev et al [7] and Thiebaut & Sentchev [8] used a towed Acoustic Doppler Current Profiler (ADCP) to obtain one of the few spatial datasets measured at the site. Comparison against the results of a two-dimensional hydrodynamic model evidenced a 20% overestimation in the modelled ebb current speeds over the area where the highest velocities are attained in the strait.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These works paved the way for more recent studies such as [15][16][17]. Very recently, and crucially for this paper dealing with the Alderney Race, the results of mainly two French research programs (THYMOTE and HYD2M) were published, most of them in a special issue of the Philosophical Transaction of the Royal Society A [18][19][20][21][22][23][24][25]. All these works will be extremely valuable for the forthcoming computations applied to farm configurations in the Alderney Race and specifically for the configuration treated in the present paper.…”
Section: Introductionmentioning
confidence: 93%
“…In each streamwise section, the mean streamwise velocity component U is calculated along the vertical rotor diameter (z * ∈ [2.56 : 5.44]), at y = 0 (figure 3 -left). Dashed-lines correspond to the U f ree component, while solid-lines The free mean flow profiles are compared to those measured in the Alderney Race [44] where the velocity profile follows the power law:…”
Section: Turbine Blockage Effect On the Mean Velocity Componentsmentioning
confidence: 99%